Implementasi Kurikulum Merdeka: Pembelajaran Kontekstual Berbasis Outdoor Learning Pada Materi Penginderaan Jauh - Alfiani Dwi Astuti (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2025)
Increasing student activity and learning outcomes by implementing the outdoor learning method as an implementation of the independent curriculum is the objective of this study. Classroom Action Research is the type of research used and consists of Cycle I and Cycle II. The study was conducted at SMA Negeri 2 Selayar with X5 as the subject of the study. The instruments used in this study were observation sheets, documentation, and test assessment sheets. The data was analyzed descriptively qualitatively, where the research results obtained would be described qualitatively. From the results of the study, it was found that there was a significant increase in student activity from cycle I to cycle II, increasing from 64.98% to 89.98%. Similarly, the learning outcomes of students in class X5 of SMA Negeri 2 Selayar also increased significantly from 53.3% in cycle I and increased to 90% in cycle II. So it can be concluded that the learning evaluation carried out in cycle I and improvements in cycle II have been successful.